NON-STEROIDAL ANTI-INFLAMMATORY DRUGS AND ESSENTIAL OILS IN THE TREATMENT OF GUM AND MUCOSAL DISEASES - Denisa Marin Batir; Irina Adriana Beuran; Gabriel Valeriu Popa; Anamaria Zaharescu; Daniela Mihalache (Romanian Journal of Oral Rehabilitation)
Gum and mucosal diseases are characterized by inflammatory processes that require effective treatment to reduce pain and prevent complications. Non-steroidal anti-inflammatory drugs (NSAIDs) are the main therapeutic solution, acting by inhibiting cyclooxygenase and reducing the synthesis of prostaglandins. However, their prolonged use can cause gastrointestinal and renal adverse effects. In this context, essential oils have gained attention due to their anti-inflammatory, antimicrobial and antioxidant properties. Compounds such as eugenol, thymol and carvacrol have demonstrated effectiveness in reducing inflammation and oxidative stress, having a superior safety profile. The comparison of the two therapeutic classes highlights the rapid effectiveness of NSAIDs in acute inflammation, while essential oils are more suitable for adjuvant therapies and chronic inflammation. Future research should explore combined formulations that maximize the benefits of both types of treatment while reducing adverse effects. The development of optimized products, such as gels and mouthwashes with NSAIDs and essential oils, can be an effective strategy for the management of gum and mucosal diseases.